Comprehensive Geriatric Assessment for younger outpatients with severe mental illness: protocol for a feasibility study. Issue 2 (21st February 2023) - Arnautovska, Urska; Siskind, Dan; Pearson, Ella; Baker, Andrea; Reid, Natasha; Kwan, Winona Wing Ling; Wang, Nancy; Gordon, Emily; Hubbard, Ruth; Warren, Nicola
Abstract : Introduction: Individuals with severe mental illness are at risk of becoming prematurely frail. There is a critical unmet need for an intervention that reduces the risk of frailty and minimises the associated negative outcomes in this population. This study aims to provide novel evidence on the feasibility, acceptability and preliminary effectiveness of Comprehensive Geriatric Assessment (CGA) to improve health outcomes among people with co-occurring frailty and severe mental illness. Methods and analysis: Twenty-five participants with frailty and severe mental illness, aged 18–64 years, will be recruited from Metro South Addiction and Mental Health Service outpatient clinics and provided with the CGA. Primary outcome measures will include the feasibility and acceptability of the CGA embedded in routine healthcare. Other variables of interest will include frailty status, quality of life, polypharmacy, and a range of mental and physical health factors. Ethics and dissemination: All procedures involving human subjects/patients were approved by Metro South Human Research Ethics Committee (HREC/2022/QMS/82272). Study findings will be disseminated through peer-reviewed publications and conference presentations.